Quadratic Inverse Function Tsallis Entropy Multi-modulus Blind Equalization Algorithm - Guo Yecai; Gong Xiuli; Chen Qu; Gong Xi (Institute of Advanced Engineering and Science, 2013)
In underwater acoustic communication systems, inter-symbol interference (ISI) caused by communication channel distortion is the main factor affecting the quality of communication. Aiming at the shortcomings of computational complexity, slow convergence rate, and poor stability of Multi-Modulus Algorithm (MMA), a quadratic inverse function Tsallis entropy of Cascade Multi-Modulus blind equalization Algorithm (TCMMA) was proposed. In the proposed algorithm, quadratic inverse function Tsallis entropy is fused with Parzen window probability density estimation method, and directly used as the cost function in cascade blind equalizer to reduce the residual mean square error, and the normalized wavelet transform is used to speed up the convergence speed. The simulation results with underwater acoustic channel show the superiority of the proposed algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2371